2014
DOI: 10.1136/annrheumdis-2013-204798
|View full text |Cite
|
Sign up to set email alerts
|

The patient perspective on remission in rheumatoid arthritis: ‘You've got limits, but you're back to being you again’

Abstract: ObjectivesThe aim of rheumatoid arthritis (RA) treatment is remission. As treatment should be targeted at outcomes relevant to patients, it is important to understand how patients perceive remission, and to assess whether the current definition of remission adequately reflects these perceptions. The objective of this study is to explore the patient perspective on remission in RA.MethodsNine focus-group discussions in Austria, The Netherlands and UK were conducted, including patients in American College of Rheu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(45 citation statements)
references
References 24 publications
1
44
0
Order By: Relevance
“…However, the meaning of remission from the patient's perspective needs to be explored further as it may differ considerably from the physician's perspective. In a recent study based on nine focus-group discussions throughout Europe, patients with RA characterized remission as decreased daily impact of their condition and the feeling of return to normality [69]. In PsA, a consensus has yet to be reached on the definitions of remission or low disease activity [70,71]; until these are agreed upon and universally accepted, it will be difficult to implement such targets in clinical practice.…”
Section: Focusing On Patients' Priorities For Treatment Goalsmentioning
confidence: 99%
“…However, the meaning of remission from the patient's perspective needs to be explored further as it may differ considerably from the physician's perspective. In a recent study based on nine focus-group discussions throughout Europe, patients with RA characterized remission as decreased daily impact of their condition and the feeling of return to normality [69]. In PsA, a consensus has yet to be reached on the definitions of remission or low disease activity [70,71]; until these are agreed upon and universally accepted, it will be difficult to implement such targets in clinical practice.…”
Section: Focusing On Patients' Priorities For Treatment Goalsmentioning
confidence: 99%
“…However, there is no consensus on the cut-off -VAS<=1 might be too restrictive and there might be discordance between patient VAS and physician VAS. Also patients' age and concurrent diseases might alter patients' opinion regarding their pain [6,8,[17][18][19][20][21]25]. The novelty of our study is the change of the inclusion criterion in the study cohort to one not quantified by a number, but by a general characterization of "return to normal" state.…”
Section: Discussionmentioning
confidence: 99%
“…Patient Reported Outcomes (PROs) were found as relevant as clinical and laboratory evaluations in disease status assessment [5,[17][18][19][20][21], adding a personal subjective touch to a scientific description of RA. A patient can clearly feel better than any index if their disease is "as good as gone".…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Optimal treatment includes shared treatment goals between health professionals and patients [16]. Van Tuyl et al reported differences in the perspective of patients and physicians on what constitutes remission [99], and different qualitative studies in RA shed light on patients' outcome preference of establishing a normal life again [100,101]. Moreover, according to patients with early RA, the above treatment strategies should far and foremost target all aspects of normality as soon as possible, providing support for the view that time is of the essence for a wider spectrum of outcomes than just the strictly medical disease outcomes in early RA [102].…”
Section: Future Aspects In the Field Of Rheumatologymentioning
confidence: 99%